Efficacy of hypertonic dextrose (prolotherapy) in early knee osteoarthritis: a short term outcome - Sethi, Anshul; Mushtaq, Muzaffar; Dagar, Pankaj; Basit, Abdul; Qureshi, Owais A. (International Journal of Research in Orthopaedics, 2024)
Background: Knee osteoarthritis (OA) is a prevalent, painful, and progressive condition significantly affecting patients' quality of life and imposing a social and economic burden. Traditionally managed through symptom relief and joint function improvement, research is increasingly focusing on disease-modifying treatments. Dextrose prolotherapy, a low-cost alternative involving the injection of a hypertonic solution, has shown promise despite limited acceptance in current guidelines. Methods: This prospective cohort study, approved by the Institutional Ethical Board of Jamia Hamdard University, assessed the effects of 12.5% hypertonic dextrose prolotherapy in 92 patients with knee OA. Patients received injections at multiple sites over a 6-week period. Outcomes were evaluated using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and visual analog scale (VAS) scores at baseline, 4, 8, 16, and 24 weeks. Results: Significant improvements were observed in both WOMAC and VAS scores. WOMAC scores decreased from 53.83 to 26.70 (p<0.0001), and VAS scores dropped from 7.12 to 3.06 (p<0.0001) at the 24-week follow-up. No major complications were noted, with minimal adverse effects reported. Improvement was consistent across all OA grades. Conclusions: Dextrose prolotherapy demonstrated substantial, sustained improvements in pain and function in knee OA patients. Given its safety, low cost, and efficacy, it represents a viable therapeutic option, especially in resource-constrained settings. Further high-quality randomized controlled trials are needed to confirm these findings and optimize treatment protocols.